2020
DOI: 10.29252/jcmh.7.1.23
|View full text |Cite
|
Sign up to set email alerts
|

The Position of a Curriculum based on the Multiple Intelligences in the Textbooks of the First Grade of Primary School based on the Components of Multiple Intelligences

Abstract: Background and Purpose: A valid curriculum must be based on the accurate understanding of the psychological dimensions of human beings. One of the most important mental aspects closely related to learning process and curriculum is the concept of intelligence. The concept of intelligence has evolved from a single concept to a multidimensional one with many forms. In this regard, Gardner's theory of multiple intelligences (2011) has established new conditions for understanding human intelligence and creating str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Categories of cultural pluralism acceptance include familiarity with the evolution of cultures, culture recognition and promotion, strengthening the power of cultures, as well as familiarity with ethnic cultural literature (2). Peaceful coexistence categories include improved intercultural relations, openmindedness, and admitting unity despite plurality (9)(10). The features of respect for divine religions in the multicultural curriculum are subcategorized as follows: familiarity with monotheistic religions' teachings and respect for the inherent dignity of human beings (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Categories of cultural pluralism acceptance include familiarity with the evolution of cultures, culture recognition and promotion, strengthening the power of cultures, as well as familiarity with ethnic cultural literature (2). Peaceful coexistence categories include improved intercultural relations, openmindedness, and admitting unity despite plurality (9)(10). The features of respect for divine religions in the multicultural curriculum are subcategorized as follows: familiarity with monotheistic religions' teachings and respect for the inherent dignity of human beings (39).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to emphasizing the necessity of multicultural themes in the curriculum, literature also confirms the gap in the current education system (25)(26)(27)(28)(29). As prior studies verified the existence of a separate subject-oriented curriculum in the primary education and with respect to the lack of a conceptual model underlying multicultural curriculum framework, the research gaps are demonstrated (9,14). In this regard, the purpose of the present research is to explain the requirements of a multicultural curriculum based on primary education objectives.…”
Section: Introductionmentioning
confidence: 99%